The Quest for Identity in African American Women’s Drama from Harlem Renaissance to the Present An Overview - Dr. Sabah Atallah Diyaiy; Hasan Mohammed Saleh (PROSPECTIVE RESEARCHES, 2023)
The concept of identity is regarded as one of the most important concepts in contemporary literature. Individuals and societies always search for an identity that gives meaning to their existence. The same is also true of African American drama. This subject occupies a central place in modern African- American drama, a hotly debated subject not only by male playwrights but also by female playwrights. Female playwrights attempt to show the importance of returning to roots as an outlet for the identity crisis they experience. Therefore, the present paper aims at giving an overall view of the subject of identity in African-American culture with particular focus on African American women playwrights. It examines the quest for identity from the Harlem Renaissance to contemporary drama along with different examples to explore how the question of identity is tackled. It has become quite oblivious that the women playwrights aim at pushing the blacks, especially the women, to feel proud of their black identity.